Distance between ROV and sea ice at the ROV station ODEN_AO2018_904-1 - Philipp Anhaus; Christian Katlein; Mario Hoppmann; Marcel Nicolaus (PANGAEA, 2020)
Along with the radiation measurements, ROV positions were obtained from acoustic LBL (Long BaseLine)-positioning and all parameters of vehicle depth, distance to the ice and attitude recorded. All times are given in UTC.
In: Anhaus, P et al. (2020): Solar radiation over and under sea ice during the Oden_AO2018 campaign (Arctic Ocean 2018: MOCCHA - ACAS - ICE) Central Arctic / North Pole drift station in 2018 on IB ODEN [dataset bundled publication]. Alfred Wegener Institute, Helmholtz Centre for Polar and Marine Research, Bremerhaven, PANGAEA, https://doi.org/10.1594/PANGAEA.925698